Pilar-pilar ekonomi Islam / Abdul Sami Al-Mishri; penterjemah, Dimyauddin Djuwaini; penyunting, Kamdani - AL-MISHRI, Abdul Saini; Juwaini, Dimyauddin; Kamdani (Pustaka Pelajar, 2006)
xxxviii, 252 hlm. ; 24 cm.